Electrophysiological tests in evaluation of glaucoma and ocular hypertension treatment – up to date knowledge. A review - Karaśkiewicz, Joanna; Lubiński, Wojciech; Penkala, Krzysztof (Klinika Oczna / Acta Ophthalmologica Polonica, 2013)
On the basis of the literature data to assess the efficacy of the electrophysiological tests (pattern electroretinogram, multifocal electroretinogram and multifocal visual evoked potentials) in evaluation of retinal ganglion cells function in glaucomatous and ocular hypertension eyes, after intraocular pressure reduction. Material and methods: Data published in the literature available at the Pub Med library between 1964–2012. Results: Several results of studies suggest, that steady-state pattern electroretinogram reveals significant improvement of retinal ganglion cells’ function after treatment with timolol, acatazolamide, beta-blockers and prostaglandin analogues. Multifocal electroretinograms’ changes, after lowering the intraocular pressure by trabeculectomy, were confirmed in only one study. There were no statistically significant correlations between changes in intraocular pressure reduction and multifocal visual evoked potentials. Conclusions: Steady state pattern electroretinogram is the most commonly used electrophysiological test in evaluating the results of glaucoma and ocular hypertension treatment.